Impact and feasibility of a self-confidence intervention among young adolescent athletes: A pilot-study - Andrea Ösp Böðvarsdóttir 1994- (2018)
Self-confidence has shown to be a key factor for success in sports, but only when it is high and stable. The aim of this pilot-study was to examine if a self-confidence intervention among young athletes in their organized sport environment was effective and feasible. The pilot-study method was both quantitative and qualitative. In the quantitative part the participants were adolescents from a handball team in Iceland, age ranged from 10 to 14 years, with mean age being 12.1. Males were 42.6% and females 57.4%. Participants answered a questionnaire at baseline measures and at follow-up. The questionnaire consisted of 21 questions, ten questions examining self-confidence, five questions about personal information and six questions about self-confidence knowledge. In the qualitative part the participants were four coaches of the adolescents. The coaches took part in semi-open interviews about the intervention, if it was feasible and if some changes to the intervention was needed. The results indicate that a self-confidence intervention was feasible among adolescents, however the intervention did not increase the adolescents’ self-confidence. Results from the baseline measures showed that 78.7% participants knew what self confidence was and 21.3% did not know what it was. Follow-up measures conducted nine weeks into the intervention showed that 100% of the participant knew what self-confidence was. Keywords: self-confidence, adolescents, intervention, handball, coaches, TROSCI. Einn af lykilþáttum velgengni í íþróttum er sjálfstraust, en aðeins þegar sjálfstraustið er gott og stöðugt. Markmiðið með þessari rannsókn var að athuga hvort sjálfstraustar íhlutun meðal ungra íþróttaiðkenda væri árangursrík og framkvæmanleg. Rannsóknarsniðið sem notast var við var bæði megindlegt og eigindlegt. Í megindlega hlutanum voru þátttakendurnir unglingar úr handbolta liði á Íslandi. Þátttakendur voru á aldrinum frá 10-14 ára, þar sem meðalaldur var 12.1 ár. Kynjahlutfallið var 42.6% drengir og 57.4% stúlkur. Þátttakendurnir ...